Evaluation of Audiometric Test Results to Determine Hearing Impairment in Patients with Rheumatoid Arthritis: Analysis of Data from the Korean National Health and Nutrition Examination Survey - Jeong, Hyemin; Chang, Young-Soo; Baek, Sun Young; Kim, Seon Woo; Eun, Yeong Hee; Kim, In Young; Lee, Jaejoon; Koh, Eun-Mi; Cha, Hoon-Suk (PLOS ONE, 2016)
This study aimed to evaluate the association between rheumatoid arthritis (RA) and hearing impairment in the Korean adult population. Audiometric and laboratory test data from the 2010–2012 Korean National Health and Nutrition Examination Survey (KNHANES) were used for analysis. The relationship between RA and hearing impairment was analyzed, adjusting for various known risk factors associated with hearing impairment. RA was defined in the questionnaire as “RA diagnosed by a physician (yes/no) through a standardized interview.” We defined hearing impairment according to 2 categories of frequency (low/mid and high) as follows (average values in kHz): low/mid frequency, 0.5, 1.0, and 2.0, and high frequency, 3.0, 4.0, and 6.0. Of the subjects, 15,158 (weighted n = 32,035,996) completed the audiometric tests. The overall weighted prevalence of RA was 1.5%. The prevalence of hearing impairment was higher in the subjects with RA than in those without RA, in both, the low/mid- and high-frequency categories (21.1% vs 7.5%, p < 0.001 and 43.3% vs. 26.2%, p < 0.001, respectively). In the multivariable logistic analysis, RA (odds ratios [OR] 1.47, 95% confidence interval [CI] 1.05–2.06, p = 0.025) was an independent risk factor of low/mid-frequency hearing impairment along with age (OR 1.12, 95% CI 1.12–1.13, p < 0.001), current smoking (OR 1.27, 95% CI 1.03–1.56, p = 0.026), and college graduation (OR 0.53, 95% CI 0.39–0.72, p < 0.001). In the multivariable analysis of high-frequency hearing impairment, RA did not show any association with hearing impairment. This study suggests that RA is associated with low/mid-frequency hearing impairment after adjustment for various known risk factors. Further study is needed to verify the hearing impairment in RA.